2023
DOI: 10.3389/fmicb.2023.1146672
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Lactobacillus plantarum ATCC14917 mitigates non-alcoholic fatty liver disease in high-fat-diet-fed rats

Abstract: Atherosclerosis and non-alcoholic fatty liver disease (NAFLD) have been increasing at an alarming rate worldwide. Many clinical studies have underlined the link between NAFLD and atherosclerosis. Our previous experiments have discovered that Lactobacillus (L.) plantarum ATCC14917 supplementation could decrease the progression of atherosclerotic lesion formation. In this study, we aimed to investigate the role of supplementation of L. plantarum ATCC14917 mitigates liver injury in rats fed with a high-fat diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The research showed the partial characterization and function of Lactobacillus plantarum L11 isolated from the feces of cats in vivo and in vitro and showed the positive effect on the modulation of fat and gut, which were also found to be positive effects in these studies [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research showed the partial characterization and function of Lactobacillus plantarum L11 isolated from the feces of cats in vivo and in vitro and showed the positive effect on the modulation of fat and gut, which were also found to be positive effects in these studies [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%